2014
DOI: 10.3109/14767058.2014.923394
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of women with a prior history of unexplained recurrent miscarriage

Abstract: Our study confirms the reassuring prognosis for achieving a live birth in the unexplained RM population with a very low incidence of adverse events with the majority delivering appropriately grown fetuses at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…There could be shared underlying risk factors for miscarriage and other adverse pregnancy outcomes. Several studies have looked at the association between the history of miscarriages and the future risk of other pregnancy complications,121314151617 but less is known about how complications might predict the future risk of miscarriage 181920…”
Section: Introductionmentioning
confidence: 99%
“…There could be shared underlying risk factors for miscarriage and other adverse pregnancy outcomes. Several studies have looked at the association between the history of miscarriages and the future risk of other pregnancy complications,121314151617 but less is known about how complications might predict the future risk of miscarriage 181920…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that the number of miscarriages—a likely indicator of the gravity of the condition—is a major determinant of the reproductive success of women with RPL; in fact, it has been reported that the live birth rates in the successive pregnancy in women with two consecutive losses is around 75% [ 4 , 5 ]. On the other hand, several studies and reviews investigating the outcome of the successive pregnancy in women with RPL found that it was burdened by many obstetric and perinatal complications which occurred more frequently than in normal control women without RPL [ 6 , 7 , 8 , 9 ], even though this finding has not been observed in all studies [ 10 ]. Therefore, it is difficult for the clinicians to ensure a clear counseling, in terms of prognosis, to women with RPL about the subsequent pregnancy once the diagnostic workup has been completed.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15% of pregnant women experience spontaneous loss of a clinically recognized pregnancy. About 1–2% of couples trying to conceive are confronted with recurrent miscarriage (RM), which is defined as three or more consecutive miscarriages before the 20th week of gestation . Several factors influence the risk of miscarriage such as maternal age and previous pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors influence the risk of miscarriage such as maternal age and previous pregnancy loss. The major known causes include antiphospholipid syndrome, abnormal parental karyotype, endocrine disorders and uterine anomalies . However, the cause of RM can only be determined in half of the patients.…”
Section: Introductionmentioning
confidence: 99%